Non-small cell lung cancer cells and concomitant cancer therapy induce a resistance-promoting phenotype of tumor-associated mesenchymal stem cells - Sentek, Hanna; Braun, Annika; Budeus, Bettina; Klein, Diana (Frontiers in Oncology, 2024)
The tumor microenvironment gained attraction over the last decades as stromal cells significantly impact on tumor development, progression and metastasis, immune evasion, as well as on cancer therapy resistance. We previously reported that lung-resident MSCs were mobilized and activated in non-small cell lung cancer (NSCLC) progression, and could even mediate radiation resistance in cocultured NSCLC cells. Here, we investigated how MSCs were affected by NSCLC cells in combination with cancer (radiation) therapy in indirect co-cultures using tumor-conditioned medium and transwells or direct three-dimensional NSCLC-MSC spheroid co-cultures in order to unravel the resistancemediating action of tumor-associated MSCs. Although no obvious phenotypic and functional alterations in MSCs following NSCLC co-culture could be observed, MSC senescence was induced following co-applied radiotherapy (RT). Global gene expression profiling in combination with gene set enrichment analysis of upon treatment was used to confirm the senescent phenotype of irradiated MSC, and moreover to reveal relevant senescence associated secretory phenotype (SASP) factors that could meditate NSCLC RT resistance. We identified senescent tumor associated-MSCs derived serine proteinase inhibitor (serpin) E1/ PAI1 as potential SASP factor mediating NSCLC progression and RT resistance. Thus, specified intra-tumor-stroma interactions and cell type-specific pro-tumorigenic functions could not only improve lung cancer classification, it could even be used for a more precise profiling of individual patients and finally paving an additional way for the discovery of potential drug targets for NSCLC patients.